Szanse zagospodarowania obszarów wiejskich związane z odnawialnymi źródłami energii - Pultowicz, Alicja; Więznowska, Katarzyna (Chances of Rural Areas Development Connected with Renewable Sources of Energy, 2005)
The accession to the European Union calls for an intensified activity in supporting the concept of sustainable development, which involves renewable sources of energy. The main renewable sources of energy in Lower Silesia voivodship, which may be used in regions with infertile soil, is wind energy, biofuel and biomass. This activity can be a great chance to create new work places, receive funds from the EU and improve general situation in impoverished rural areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 234-238